Bioinformatic analyses of hydroxylated polybrominated diphenyl ethers toxicities on impairment of adrenocortical secretory function - Zemin Cai; Wei Hu; Ruotong Wu; Shukai Zheng; Kusheng Wu (Komiyama Printing Co. Ltd, 2022)
Background: Polybrominated diphenyl ethers (PBDEs) and their metabolites have severe impact on human health, but few studies focus on their nephrotoxicity. This study was conceived to explore hub genes that may be involved in two hydroxylated polybrominated diphenyl ethers toxicities on impairment of adrenocortical secretory function. Methods: Gene dataset was obtained from Gene Expression Omnibus (GEO). Principal component analysis and correlation analysis were used to classify the samples. Differentially expressed genes (DEGs) were screened using the limma package in RStudio (version 4.1.0). Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Reactome enrichment analyses of DEGs were conducted. Protein-protein interaction (PPI) network was established using STRING network, and genes were filtered by Cytoscape (version 3.8.2). Finally, the hub genes were integrated by plug-in CytoHubba and RobustRankAggreg, and were preliminarily verified by the Comparative Toxicogenomics Database (CTD). Results: GSE8588 dataset was selected in this study. About 190 upregulated and 224 downregulated DEGs in 2-OH-BDE47 group, and 244 upregulated and 276 downregulated DEGs in 2-OH-BDE85 group. Functional enrichment analyses in the GO, KEGG and Reactome indicated the potential involvement of DEGs in endocrine metabolism, oxidative stress mechanisms, regulation of abnormal cell proliferation, apoptosis, DNA damage and repair. 2-OH-BDE85 is more cytotoxic in a dose-dependent manner than 2-OH-BDE47. A total of 98 hub genes were filtered, and 91 nodes and 359 edges composed the PPI network. Besides, 9 direct-acting genes were filtered for the intersection of hub genes by CTD. Conclusions: OH-PBDEs may induce H295R adrenocortical cancer cells in the disorder of endocrine metabolism, regulation of abnormal cell proliferation, DNA damage and repair. The screened hub genes may play an important role in this dysfunction.